Pengaruh Struktur Modal Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Prihadi Dwianggoro (Jurnal Ilmiah Wahana Pendidikan, 2022)
Purpose. This study aims to examine and analyze the effect of capital structure and dividend policy on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2010-2019 period. Methods. The method used is the Associative method. The number of samples used as many as 10 companies using purposive sampling. The data used in this study is secondary data. Data analysis method using multiple linear regression. Findings. The results showed that partially the capital structure had a positive and significant effect on firm value. Partially dividend policy has a positive and significant effect on firm value. Simultaneously capital structure and dividend policy have a positive and significant effect on firm value. Implication. If investors want to invest in shares in a company, the variables of capital structure and dividend policy can be considered because based on the results of this study, these two variables have a positive and significant influence on firm value